Parental Autonomy Support, Parental Psychological Control and Chinese University Students’ Behavior Regulation: The Mediating Role of Basic Psychological Needs - Wei, Songqin; Teo, Timothy; Malpique, Anabela; Lausen, Adi (Frontiers in Psychology, 2022)
The present research examined relationships between parental autonomy support, parental psychological control and Chinese emerging adults’ autonomous regulation in their university studies as well as dysregulation in social media engagement. A total of 287 (102 female and 185 male) Chinese university students reported on their perceived parental styles, psychological needs and behavior regulation. Results showed that basic psychological needs satisfaction was positively associated with parental autonomy support and autonomous regulation in learning; needs frustration was positively correlated with parental psychological control and dysregulation in social media engagement. More importantly, psychological needs frustration was a mediator of the relation between parental psychological control and dysregulation in social media engagement. Our findings suggest that students living an autonomy-supportive familial environment tend to have satisfied psychological needs as well as autonomous learning behavior. Impairment of psychological needs could be one of the mechanisms through which psychologically controlling parenting was linked to dysregulation of social media use in Chinese culture.